Boys don't cry? : rethinking narratives of masculinity and emotion in the U.S. - Shamir, Milette; Travis, Jennifer, 1967- (NONE., 2002)
We take for granted the idea that white, middle-class, straight masculinity connotes total control of emotions, emotional inexpressivity, and emotional isolation. That men repress their feelings as they seek their fortunes in the competitive worlds of business and politics seems to be a given. This collection of essays by prominent literary and cultural critics rethinks such commonly held views by addressing the history and politics of emotion in prevailing narratives about masculinity. How did the story of the emotionally stifled U.S. male come into being? What are its political stakes?